Utilizing Open Spaces for community-driven Development of XR Teaching Applications in Photonics - Kretzschmar, Johannes; Best, Sabine; Zakoth, David; Voigt, Henrik; Li, Ke; Kaiser, Thomas; Geiss, Reinhard; Helgert, Christian; Pertsch, Thomas (Optics InfoBase Conference Papers, 2021)
We present an approach of developing XR teaching applications by implementing open spaces as a hub for the photonics community and developers interested in XR technologies and give a first evaluation of technologies and platforms.
CRIS-Team Scopus Importer:2023-04-20